Kesalahan Penggunaan Pasal 112 Undang-Undang Nomor 35 Tahun 2009 Tentang Narkotika Terhadap Penyalahguna Narkotika (Studi Putusan PN Nomor: 93/Pid.Sus/2018/PN.Rap Jo. Putusan PT Nomor: 413/Pid.Sus/2018/PT.MDN Jo. Putusan Kasasi Nomor: 2410 K/Pid.Sus/2018) - Dewi, Febbyola Sintya; Nurhidayat, Syarif (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
Abstract In practice, it is a well-established fact that law enforcement officers frequently make errors in distinguishing whether a criminal act constitutes narcotics abuse or narcotics trafficking. This issue is suspected to have occurred in Decision Number: 93/Pid.Sus/2018/PN.Rap Jo. 413/Pid.Sus/2018/PT.MDN Jo. 2410 K/Pid.Sus/2018. Based on this legal issue, the formulation of the problems in this research is, first, whether the Panel of Judges’ decision to convict the defendants under Article 112 Paragraph (1) of Law Number 35 of 2009 concerning Narcotics was appropriate; and second, whether the sentence imposed on the defendants was in line with the objectives of Law Number 35 of 2009 concerning Narcotics. This research is a normative juridical study using a statutory and case approach. The findings indicate that the Panel of Judges erred in applying Article 112 Paragraph (1) of Law Number 35 of 2009 concerning Narcotics in this case, as the defendants were narcotics abusers rather than narcotics traffickers. Second, the application of Article 112 Paragraph (1) of the Narcotics Law to narcotics abusers in the case a quo does not align with the principles of justice and disregards the rights of abusers to receive guaranteed rehabilitation efforts as stipulated in Article 127 Paragraph (1) of the Narcotics Law. Rehabilitation efforts are more appropriate for narcotics abusers than merely imposing imprisonment.